Curriculum design and teaching practice of Nursing Research based on BOPPPS model under the guidance of KAP concept (KAP理念指导下基于BOPPPS模型的《护理研究》课程教学设计与实践) - WANG Xiang (王翔); MIAO Yukuan (苗宇宽); MENG Yahui (孟亚慧); FANG Haiyan (方海雁) (中西医结合护理)
Objective To explore the effect of curriculum teaching of Nursing Research based on BOPPPS model under the guidance of knowledge, attitude and practice (KAP). Methods Totally114 nursing undergraduates of academic year 2020 were selected as teaching objects, including 58 in the control group and 56 in the observation group. The control group adopted the traditional teaching method, while the observation group adopted the BOPPPS teaching mode guided by the concept of KAP. At the end of the course, the scientific research knowledge of the nursing students was measured by closed-book exams and evaluation of review paper writing. A survey using self-assessment questionnaire was conducted to investigate the learning effectiveness and research ability of nursing students. The participation rate in research activities and paper submission rate were compared between two groups. Results The outcomes of closed-book exams , quiz and evaluation of review paper in the observation group were higher than those in the control group (P＜0. 05). Nursing students in the observation group achieved higher outcomes in self-assessment of learning effectiveness and research ability compared with those in the control group (P＜0. 05). The participation rate in research activities and paper submission rate in the observation group were higher than those in the control group(P＜0. 05). Conclusion Under the guidance of KAP concept, BOPPPS model can improve the teaching effect of Nursing Research courses and enhance the scientific research consciousness and ability of nursing undergraduates. (目的 探讨知识、信念与行为(KAP)理念指导下基于BOPPPS模型的《护理研究》课程教学效果。方法 选取安徽中医药大学2020级114名护理本科生为教学对象, 分为两组: 对照组58人, 观察组56人。对照组采用传统的授课方式, 观察组采用KAP理念指导下的BOPPPS教学模式。课程结束后采用考试与随堂测试的方式对护生进行考核, 并对护生综述撰写质量进行评分。采用自制的学生学习效果自我评价表和科研能力自评量表对两组护生进行问卷调查。统计和比较两组护生本学期科研活动参与率及论文投稿率。结果 观察组护生期末成绩、随堂考核成绩和综述成绩得分高于对照组, 差异有统计学意义(P＜0. 05); 观察组护生学习效果自我评价和科研能力自我评价结果优于对照组, 差异有统计学意义(P＜0. 05); 观察组护生科研活动参与率和文章投稿率均高于对照组(P＜0. 05)。结论 KAP理念指导下基于BOPPPS模型可以提高《护理研究》课程的教学效果, 提高护理本科生的科研意识与能力。)